Pengaruh Kualitas Produk, Brand Image, Brand Ambassador, Content Marketing, Price Bundling Terhadap Keputusan Pembelian Produk Kosmetik Glad2glow (Studi Pada Konsumen G2g Di Jember) - Anggia Davanya Fabianti; Agustin HP; Muhdar (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This research aims to test and analyze the influence of product quality, brand image, brand ambassador, content marketing, and price bundling on purchasing decisions for Glad2Glow cosmetic products. The type of research used in this research is quantitative. The research population includes all Glad2glow consumers in Jember with a total sample of 60 samples using purposive sampling. The data analysis methods used are instrument tests, classical assumption tests, multiple linear regression tests, analysis of the coefficient of determination (R2) and hypothesis testing. Based on the results of the analysis, the results of the t test research show that the product quality, brand ambassador and price bundling variables have a positive and significant effect on purchasing decisions, while the brand image and content marketing variables have a significant and negative effect on purchasing decisions. The research shows that the F test variables product quality, brand image, brand ambassador, content marketing, and price bundling simultaneously influence purchasing desicions